Perencanaan dan Pengelolaan Produk sebagai Kunci Sukses: Analisis Faktor Keberhasilan - Ermina Waruwu; Johannes Sohirimon Lumbanbatu; Din Oloan Sihotang; Meri Mariani Lumban Gaul; Mariana Siregar; Elonike Br Bangun (Ilin Institute, 2024)
This training aims to identify the understanding of Catholic youth at St. Peter and Paul Parish, Kabanjahe, regarding Successful Business Planning Strategies in relation to Product Management and Business Success Factors. The training was conducted through the stages of planning, preparation, implementation, and evaluation. The products produced by the training participants were categorized as Good, with an average score of 377. The comprehension test showed a t-statistic value of 4.652 for the influence of Successful Business Planning Strategies on Product Management, and 15.960 for Business Success Factors, both exceeding the established t-table value. These results indicate that this community service activity plays an important role in enhancing Catholic youth’s understanding of business strategies and success, which is expected to support economic self-sufficiency at St. Peter and Paul Parish, Kabanjahe.